1970
DOI: 10.1021/jo00836a016
|View full text |Cite
|
Sign up to set email alerts
|

O-quinone methides. II. Trapping with production of chromans

Abstract: Typical Rearrangement.-To a constricted tube with a small magnetic stirrer was added 0.26 g (0.001 mol) of 1 followed by 5 ml of dry hexane and 1.3 ml of 1.6 N (0.002 mol) nbutyllithium-hexane. The tube was purged with nitrogen, sealed and placed in a bath at 75 ± 2°with stirring for 48 hr. Water (3 ml) was added to the reaction mixture, and the organic layer was separated and extracted with 3 N HC1. The remaining nonbasic phase was retained for further analysis. The acid extracts were made basic with 50% sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 5 publications
1
21
0
1
Order By: Relevance
“…QMs are too reactive to be stored, so they have to be generated in situ. Methods to prepare QMs in thermal reactions rely on the oxidation of phenols, dehydration from hydroxybenzyl alcohols, elimination of nitriles from 1,2‐benzoxazines, and fluoride‐induced desilylation . Photochemical methods are more interesting, particularly in biological systems, as they enable access to QMs under much milder conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…QMs are too reactive to be stored, so they have to be generated in situ. Methods to prepare QMs in thermal reactions rely on the oxidation of phenols, dehydration from hydroxybenzyl alcohols, elimination of nitriles from 1,2‐benzoxazines, and fluoride‐induced desilylation . Photochemical methods are more interesting, particularly in biological systems, as they enable access to QMs under much milder conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] QMs are too reactive to be stored, so they have to be generated in situ. Methods to prepare QMs in thermal reactions rely on the oxidation of phenols, [37] dehydrationfrom hydroxybenzyl alcohols, [38,39] elimination of nitriles from 1,2-benzoxazines, [40] and fluoride-induced desilylation. [22,41] Photochemical methodsa re more interesting, particularly in biological systems,a st hey enablea ccess to QMs under much milder conditions.P hotochemical methods to generate QMs include the photoelimination of HF [42] or acetic acid, [43] photodeamination from the Mannich salts of the corresponding phenols, [19,44] phototautomerization of suitably substituted phenols [45,46] or naphthols, [47] and photohydration of alkenes.…”
Section: Introductionmentioning
confidence: 99%
“…22 Thus, we have recently shown that the antiproliferative activity of QMs formed in the phototautomerization of hydroxyphenylanthracenes is due to the reaction with intracellular proteins, rather than with DNA. 23 Formation of QMs often requires harsh conditions such as elevated temperature, 24,25 or the use of biologically inacceptable oxidants 26 or F − . 13 On the contrary, photochemical reactions require mild conditions which allow for the generation of QMs in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods of ortho-quinone methide generation have been reported (2), including pyrolysis of ortho-(methoxyaky1)-or ortho-(hydroxyaky1)phenols (3, 6-8, 12, 13), dehydrohalogenation of 2-chloromethylphenol (4,20), one-electron oxidation of ortho-substituted phenols (5,9), desilylation of disilylated ortho-hydroxybenzyl alcohol (15), photochemical decarbonylation of benzofuran-2(3H)-one (10) and treatment of ortho-(1-(alkylthio)alkyl)phenols with a variety of metal oxides under mild conditions (1 1, 16, 17). Recently we reported the preparation of a variety of orthoalkyl, ortho-akoxakyl, and ortho-thioakyl phenols from 2-phenyl-4H-1,3,2-benzodioxaborins, presumably via the quinone methide intermediate (21).…”
Section: Introductionmentioning
confidence: 99%